A DESCRIPTIVE ANALYSIS OF COMMON GRAMMATICAL ERRORS IN UNDERGRADUATE EFL WRITING - Adxamkhoja Abdullakhojayev; Tursunov Muhammad Ziyoxon Ilxomjon o‘g‘li (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article provides a descriptive analysis of common grammatical errors in the written work of undergraduate students learning English as a Foreign Language (EFL) and proposes effective pedagogical methods to address them. The study is based on corpus-based research and internationally conducted EFL studies. The causes and main types of grammatical errors, along with methodological approaches to reducing them, are examined, and strategies for enhancing grammatical accuracy and fluency in students’ written discourse are discussed.